Era Digital dan Evolusi Paradigma Media: Tinjauan Kritis atas Adaptasi Media Lama dalam Ekosistem Media Baru - Yusnaini Yusnaini; Hayatun Nufus; Rahmat Saleh; Wahyu Adi Setyo Wibowo (Society, 2025)
This study examines the paradigm shift of traditional media in the face of the digital era, focusing on the adaptation processes and forms of media convergence through Norman Fairclough's Critical Discourse Analysis (CDA) approach. The research analyzes the discourse representations of digitalization constructed by four media institutions, BBC, TVRI, Kompas, and The Guardian, through official documents, corporate statements, and strategic content. This study aims to explore how traditional media constructs its identity in response to the demands of digital platforms and how the power structures and ideologies behind this transformation process unfold. The main findings reveal that media transformation is not only technical but also reflects changes in power structures, ideological values, and epistemic dynamics. At the textual level, media adaptation is constructed through narratives of innovation and participation, yet it retains the institutional dominance of traditional media. At the level of discursive practices, media institutions adopt multiplatform strategies and user engagement; however, public participation remains structurally controlled by the media organizations. Meanwhile, at the social practice level, there is a negotiation between traditional journalistic values and the increasingly dominant digital algorithmic logic in content management. The shift in media paradigms from linear, centralized communication models to participatory, modular, and decentralized many-to-many communication models has introduced new challenges, such as epistemic crises, misinformation, and digital platform dominance. Despite this, traditional media still strives to maintain its relevance in the increasingly complex digital media ecosystem. This study contributes theoretically by recommending the need for deeper critical digital literacy, as well as a reformulation of journalistic values to address the challenges of misinformation and technological dominance. An interdisciplinary approach is essential to better understand communication within the contemporary media landscape, which is increasingly dominated by digital platforms.